Relevance of Ambedkar's ideology - Kataria, Kanta (Rawat, 2015)
Dr. B.R. Ambedkar was a thinker-activist, and his ideology is very much relevant to the social and political milieu of Indian society. What is striking is that the relevance of his ideology is gaining momentum. Based on primary and secondary sources, this book is a significant contribution to the understanding of Ambedkar's life, ideology, and mission. The book asserts that Ambedkar continues to attract attention because of his liberal, pragmatic, and far-sighted ideology, aiming towards the transformation and reconstruction of Indian society as an organic whole. His social and political ideology is not only a plan of salvation for the downtrodden, but it is also meant to promote fraternity and social solidarity. Various concepts of B.R. Ambedkar - such as democracy, a just society, nation-building, social justice, a true religion, human rights, and revival of Buddhism, etc. - are clearly expressed. [Subject: India Studies]